REVEALING THE CAUSES OF STUDENTS' ERRORS IN INTEGER ARITHMETIC OPERATIONS: COGNITIVE AND GENDER PERSPECTIVES - Robial Robial; Sunismi Sunismi; Anies Fuady (Universitas Bhinneka PGRI, 2025)
The low understanding of integer arithmetic operations often leads students to make mistakes when solving math problems. This study aims to identify various types of cognitive errors experienced by students based on Nolting's theory, and to analyze their relationship to gender differences. The research method used is descriptive qualitative, with data collection conducted through diagnostic tests on 58 students and in-depth interviews with 10 grade VII students of MTs N 1 Sarolangun. According to Nolting, the five categories of errors analyzed in this study include: Misread-Directions Errors, Careless Errors, Concept Errors, Application Errors, and Test-Taking Errors. The research findings show that the most common errors are Careless Errors and Concept Errors, with female students making more errors in each category than male students. These findings emphasize the importance of analyzing comprehensive errors and the need for a learning approach that considers cognitive and gender factors to improve the quality of mathematics learning.